SCIENTIFIC AND THEORETICAL BASIS OF VOLUNTEER ACTIVITY - Tolibov Bekzod Khakimovich; Vahabova Tillakhan Khakimjanovna (Web of Journals Publishing, 2025)
This article analyzes the essence of volunteering as a type of human activity based on classical literature. It also systematizes theoretical views related to volunteering.
Keywords: Volunteering, social capital, adaptive functions, the concept of